2110. Taurolidine-Citrate Lock Solution for the Prevention of Central-Line-associated Bloodstream Infection (CLABSI) in Pediatric Hematology-Oncology and Gastrointestinal Failure Patients with High Baseline CLABSI Rates. (26th November 2018) - Chong, Chia Yin; Ong, Rina Yue Ling; Tan, Natalie Woon Hui; Seah, Valerie Xue Fen; Chan, Mei Yoke; Soh, Shui Yen; Ong, Christina; Lim, Ashley Shi Yuan; Thoon, Koh Cheng
Abstract: Background: Catheter- line-associated bloodstream infection (CLABSI) is a serious complication of patients on long-term central venous catheters (CVC). Taurolidine-citrate solution (TCS) is a catheter-lock solution with broad- spectrum antimicrobial action that prevents biofilm formation. The aim of this study was to evaluate the efficacy of TCS in reducing CLABSI rate in pediatric patients with long-term CVC at a tertiary children's hospital. Methods: This was an open-label trial of hematology-oncology (H/O) and gastrointestinal (GI) inpatients with the following inclusion criteria: Pediatric patients < 17 years of age, at least 1 previous CLABSI, required long-term CVC, e.g., long-term parenteral nutrition or undergoing chemotherapy for malignancy and have a minimum dwell time of at least 8 hours for TCS. The period of surveillance was from each patient's first CVC insertion till December 14, 2017 or discontinuation of TCS. CLABSI was calculated based on the number of CVC-associated BSI per 1, 000 catheter-days. Statistics were derived using SPSS 19.0 and the student T -test for paired samples and nonparametric Wilcoxon analysis for two-related-samples test with a P value of < 0.05. OpenEpi v3.01 was used to compare 2 person-time rates and rate ratios with 95% confidence intervals. Results: Thirty-four patients were recruited with a median age of 3.4 years (IQR 1.5–10.1 years). H/O patients constituted 58.8% ( n = 20) and GI patients 41.2% ( n = 14). The majority of CVC were Hickman line ( n = 16, 47.1%) followed by Port-a-Cath ( n = 8, 23.5%) and PICC ( n = 10, 29.4%). The median duration of TCS usage was 138 days (IQR 62.50–307.25 days). The longest duration of TCS was 1737 days (4.8 years). Median pre- and post-TCS CLABSI rates for the whole cohort, H/O and GI patients were 14.92 ± 13.50 and 2.65 ± 4.31 ( P < 0.001); 16.55 ± 12.96 and 2.81 ± 4.66 ( P < 0.001); 12.59 ± 14.39 and 2.42 ± 3.91 ( P = 0.011) per 1000 catheter days respectively. For the whole cohort, pre and post-TCS rate ratio was 0.20 (95% CI 0.12–0.33, P < 0.001). TCS reduced markedly the risk of CLABSI for the whole cohort by 80%; for H/O patients by 79% and GI patients by 88%. Conclusion: Taurolidine-citrate solution was highly successful in reducing CLABSI rates by 80% in patients on long-term CVC with high baseline CLABSI rates. Disclosures: All authors: No reported disclosures.